2016
DOI: 10.1007/s11743-016-1835-6
|View full text |Cite
|
Sign up to set email alerts
|

Advantage of Sodium Polyoxyethylene Lauryl Ether Carboxylate as a Mild Cleansing Agent

Abstract: Five anionic surfactants widely used in commercial skin cleansers were studied: sodium polyoxyethylene lauryl ether carboxylate (EC), sodium polyoxyethylene alkyl ether sulfate (ES), sodium dodecyl sulfate, potassium laurate, and N-cocoyl-L-glutamic acid monosodium salt. The amount of surfactant from aqueous solution adsorbed into the stratum corneum (SC), the degree of SC swelling, the change of the secondary structure of SC proteins (denaturation). The surface tension of surfactant-zein mixed solutions, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
6
9
0
Order By: Relevance
“…Furthermore, weak repulsion between surfactants adsorbed on the protein induces minor changes in the protein secondary structure. The above findings are consistent with the observations made by Ozawa et al (Ozawa et al, ) in their study of five anionic surfactants. The authors correlated their findings using the zein test with the results of surface tension and stratum corneum adsorption.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, weak repulsion between surfactants adsorbed on the protein induces minor changes in the protein secondary structure. The above findings are consistent with the observations made by Ozawa et al (Ozawa et al, ) in their study of five anionic surfactants. The authors correlated their findings using the zein test with the results of surface tension and stratum corneum adsorption.…”
Section: Resultssupporting
confidence: 94%
“…Surfactants with a reduced charge density of the hydrophilic part (polar head) due to the presence of an additional hydrophilic part in the structure (ethylene oxide or hydroxyl groups) are less irritant to the skin. This type of structure not only limits electrostatic interactions between the electrically charged protein and surfactant parts, but also eliminates interactions between the hydrophobic fragments of surfactant and protein molecules (Chen et al, ; Ozawa et al, ; Seweryn, ; Zhou et al, ). Also, surfactants with larger‐sized functional groups are characterized by a considerably lower capacity to adsorb on the surface of proteins, which significantly reduces their negative impact on the protein structure.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorbed amount was the lowest for EC, and the degree of swelling was also the smallest. This result corresponds well with the behavior observed in our previous in vitro study using SC powder collected from human heels (Ozawa et al, ); particularly, little adsorption and small SC swelling for EC were again observed in this in vivo experiment.…”
Section: Discussionsupporting
confidence: 92%
“…The following measurements/evaluations were made: quantitative analysis of (i) the amount of adsorbed surfactants in the SC, (ii) the amount of dissolved amino acids and the remaining amount of ceramides (one of the representative components in intercellular lipids), (iii) denaturation of SC proteins in the forearm skin evaluated using in vivo Fourier‐transform infrared spectroscopy (FT‐IR) (Brancaleon et al, ; Dong et al, ; Rastogi and Singh, ; Surewicz et al, ; Yadav et al, ), (iv) SC swelling after the skin soak test measured using confocal Raman spectroscopy (Caspers et al, ; Egawa and Kajikawa, ; Egawa and Tagami, ; Nakagawa et al, ), and (v) dermoscopic evaluation of SC functions (water‐retention capability and barrier function) and visual assessment of skin conditions (dryness and redness). The overall in vivo results supported the excellent performance of EC as a mild cleansing surfactant base that was proposed from our previous in vitro analysis (Ozawa et al, ); direct evaluation of skin functions and conditions strongly confirmed our claim. Furthermore, a possible mechanism of the mildness of the EC solution to the SC was discussed from the viewpoint of the SC swelling depth and turnover rate.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation